Um vazio me chama da praça ao porão, uma experiência de invenção de público no Theatro José de Alencar: estudo de caso do Projeto Porão - Gurgel, Izabel Rosa Barbosa (2004)
A cartography of the Porão Project, held at the Theatro José de Alencar, in Fortaleza, from May 2001 to December 2002. It aims to problematize the notion of the public with which it operates in the field of cultural production. Beyond the public As a demand to be served, a target to be reached. It operates in the perspective of which public is a social construction. Public is created, invented, produced. The relationship that underlies this perspective is that of theater and processes of subjectivation. As an audience-building program, developed by a cultural institution of Public, governmental, can establish vital social practices? The inquiry leads to empirical research, conducted over the life of the project. It permeates the dialogue with the sociology of Pierre Bourdieu, with an emphasis on the understanding of learning by the body. The understanding of subjectivity as a social process, as eminently gestated in the social, comes from Deleuze-Guattari. It points to an understanding of the public in the field of production. An understanding that Public the role of artist, creator of new demands, social agent of the permanent invention of life.